Coralligenous habitat: patterns of vertical distribution of macroalgal assemblages - Piazzi, Luigi; Balata, David (Scientia Marina, 2011)
The present study investigates patterns of distribution of macroalgal coralligenous assemblages in relation to depth and evaluates the role of different environmental conditions on these patterns. Two depths (30 and 40 m) were investigated off small islands and off continental coasts in order to select two different environmental conditions. Results showed differences between depths in the structure of assemblages around islands, while along the continental coasts these patterns were not evident. Moreover, differences between assemblages related to different environmental conditions were more evident in the shallower zone of distribution of the coralligenous habitat. This correlative study did not allow us to identify any cause-effect relationship, but patterns we detected agree with those of other studies, suggesting that alterations in the environmental conditions may be the cause of the decrease in differences among assemblages developing at different depths and may lead to a higher spatial homogenization and an impoverishment of the whole subtidal system.